Analysis of the postharvest storage characteristics of the new red-fleshed apple cultivar 'meihong'. (30th August 2021) - Lu, Le; Zuo, Weifang; Wang, Cuicui; Li, Cuixia; Feng, Tian; Li, Xi; Wang, Chao; Yao, Yuxin; Zhang, Zongying; Chen, Xuesen
Highlights: The critical roles of ACS1 genotype and ethylene in 'Meihong' fruits were identified. Low temperature storage with 1-MCP treatment can effectively maintain fruit qualities. Vitamin C, phenolic compounds and antioxidant activities remained at high levels during storage. Abstract: This study examined the effects of postharvest storage conditions on the fruit quality of a new red-fleshed apple cultivar ('Meihong'). Mature 'Meihong' and 'Golden delicious' apples were exposed to room temperature, low temperature, and low temperature and 1-MCP, after which several fruit characteristics were evaluated (i.e., firmness, ethylene release rate, relative content of aroma components, phenolic compounds and antioxidant capacity, fruit softening-related enzyme activities, and related gene expression). Both 'Meihong' and 'Golden delicious' were ACS1-1/-2 heterozygotes, but the ethylene release rate in 'Meihong' fruits was lower than that in 'Golden delicious' fruits during storage. Therefore, 'Meihong' fruits are more conducive to storage. The low temperature storage with and without 1-MCP delayed fruit softening, decreased the ethylene release rate and ester aroma component content, and maintained total flavonoid and anthocyanin contents. Therefore, storage at low temperatures with 1-MCP or other preservatives may be useful for maintaining the 'Meihong' fruit quality.